Investigación acerca de la naturaleza de la mente (capítulo 96, libro III del Yoga-Vāsiṣṭha) - Hernández Quiroz, Anselmo (El Colegio de México, 2013)
Translation from Sanskrit of chapter 96 of Yoga-Vāsiṣṭha’s third book, by Anselmo Hernández Quiroz.